Urban stormwater and flood management. Enhancing the liveability of cities. - (:unkn) unknown (Springer, 2019)
This book brings together the experiences of engineers and scientists from Australia and the United Kingdom providing the current status on the management of stormwater and flooding in urban areas and suggesting ways forward. It forms a basis for the development of a framework for the implementation of integrated and optimised storm water management strategies and aims to mitigate the adverse impacts of the expanding urban water footprint. Among other topics it also features management styles of stormwater and flooding and describes biodiversity and ecosystem services in relation to the management of stormwater and the mitigation of floods. Furthermore, it places an emphasis on sustainable storm water management measures. Population growth, urbanisation and climate change will pose significant challenges to engineers, scientists, medical practitioners, policy makers and practitioners of several other disciplines. If we consider environmental and water engineers, they will have to face challenges in designing smart and efficient water systems which are robust and resilient to overcome shrinking green spaces, increased urban heat islands, damages to natural waterways due to flooding caused by increased stormwater flow. This work provides valuable information for practitioners and students at both senior undergraduate and postgraduate levels.
Keywords: Stadtplanung; Regenwasserbewirtschaftung; Regenwassermanagement; Wassermanagement; Überflutung; Überschwemmung; Hochwasserschutz; Stadtentwässerung; Klimaanpassung; Resilienz; Vorsorge; Technische Infrastruktur